2013
DOI: 10.1186/1478-7547-11-21
|View full text |Cite
|
Sign up to set email alerts
|

A cost-effectiveness analysis of a 10-valent pneumococcal conjugate vaccine in children in six Latin American countries

Abstract: BackgroundA recently developed 10-valent pneumococcal non-typeable H influenzae protein D-conjugate vaccine (PHiD-CV) is expected to afford protection against more than two thirds of isolates causing IPD in children in Latin America, and also against acute otitis media caused by both Spn and NTHi. The objective of this study is to assess the cost-effectiveness of PHiD-CV in comparison to non-vaccination in children under 10 years of age in Argentina, Brazil, Chile, Colombia, Mexico and Peru.MethodsWe used a st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 37 publications
3
38
0
2
Order By: Relevance
“…Thus, some studies have shown that children vaccination against pneumococcus is cost-effective from the perspective of society, reduces the total burden of pneumococcal disease, including CAP. Martí et al11 analyzed the cost-effectiveness based on quality-adjusted life year (QALY) of PCV-10 in six Latin American countries, including Brazil, and reported that the incorporation of immunization is a cost-effective strategy in improving health standards of the pediatric population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, some studies have shown that children vaccination against pneumococcus is cost-effective from the perspective of society, reduces the total burden of pneumococcal disease, including CAP. Martí et al11 analyzed the cost-effectiveness based on quality-adjusted life year (QALY) of PCV-10 in six Latin American countries, including Brazil, and reported that the incorporation of immunization is a cost-effective strategy in improving health standards of the pediatric population.…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, with the incorporation of pneumococcal vaccines, particularly 10-valent, since 2010,6 , 7 there is a reduction of pneumococcal diseases, such as meningitis and CAP,8 - 10 in children under two years of age, with a decline in the number of hospitalizations, malnutrition, deaths, and parental work absenteeism, as well as cost reduction, among others 1112 …”
Section: Introductionmentioning
confidence: 99%
“…Rates of service utilizations were obtained from Delphi panels [15,23], as previously described [14]. Costs (Additional file 1: Table S6) were obtained in 2009 Nuevos Soles and translated to 2009 US$ using the exchange rate for December 2009 (US$ 1 = 2.78 Nuevos Soles).…”
Section: Methodsmentioning
confidence: 99%
“…EEs concur [54,55]. In Argentina [56], Uruguay [57], and Brazil [58,59] PCV was shown to be more cost-effective than the nonvaccination scenario.…”
Section: Discussionmentioning
confidence: 99%